Recent advances in understanding the effects of T lymphocytes on mucosal barrier function in allergic rhinitis - Yang, Maolin; Sun, Liwei; Zhu, Dongdong; Meng, Cuida; Sha, Jichao (Frontiers in Immunology, 2023)
Allergic rhinitis is a non-infectious chronic inflammatory disease of the nasal mucosa that affects T cells and their cytokines. T cells play significant roles in the development of allergic inflammatory diseases by orchestrating mechanisms underlying innate and adaptive immunity. Although many studies on allergic rhinitis have focused on helper T cells, molecular makeup, and pathogenesisrelated transduction pathways, pathological mechanisms have not yet been completely explored.Recent studies have suggested that T cell status may play an important role in the interaction between T cells and the nasal mucosal barrier in allergic rhinitis. This study aimed to explore the interactions between T cells and nasal mucosal barriers in allergic rhinitis and to review the therapeutic modalities of pertinent biological agents involving T cells.